Leader ethical voice and subordinate job performance: the chain mediating role of subordinate identification with leader and leader-member exchange - Xia, Fubin; Lu, Ping; Wang, Lifang (Frontiers in Psychology, 2024)
Introduction Ethical voice is a valuable ethical behavior that enables organizations to promptly recognize and rectify unethical issues and practices, thus preventing severe dilemmas and crises. Despite its importance, the extant literature has yet to fully explore the impact of a leader’s ethical voice on subordinate outcomes. This study bridges this gap by integrating social identity theory and social exchange theory to scrutinize the process by which a leader’s ethical voice affects subordinate task performance. Methods We employ a serial mediation model to explore the mechanisms by which a leader’s ethical voice enhances subordinates’ task performance. Our theoretical framework is empirically validated using a dataset that includes 449 subordinate-leader pairings from Chinese enterprises. Results The survey results demonstrate that a leader’s ethical voice has a significant positive impact on subordinate task performance. Subordinate identification with leader and leader-member exchange not only individually mediate the effects of a leader’s ethical voice on subordinate task behavior but also jointly serve as a chain-mediated mechanism in the influence of a leader’s ethical voice on subordinate task behavior. Discussion These findings illuminate the substantial effects that ethical leadership behaviors exert on employee performance and offer fresh perspectives on the intricate dynamics that govern this influence.